2017
DOI: 10.1108/et-01-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial education at university level and entrepreneurship development

Abstract: Purpose The purpose of this paper is to contribute to the literature on effectiveness of entrepreneurship education by empirically assessing the role of university entrepreneurial education in entrepreneurship development and reporting the results. Design/methodology/approach A quantitative method was applied for this study. This research was preplanned and structured. Based on the previous literature, hypotheses have been developed. The sample is composed on the basis of a simple random sampling and consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 69 publications
(74 reference statements)
3
76
0
5
Order By: Relevance
“…Their probability values are less than 5% level of significance (p-value < 0.05). This result is similar to thw studies of Hasan et al (2017) and Shahid et al (2017). On the other hand, 'Entrepreneurship course has enhanced my ability to identify opportunities (X2)', 'My university environment encourage me to engage in entrepreneurial activities (X4)', and 'The atmosphere at my university inspires me to develop new business ideas (X5)' are not statistically significant in influencing the level of entrepreneurial interest (Yi) of MBA students at 5% level of significance.…”
Section: 3supporting
confidence: 69%
See 2 more Smart Citations
“…Their probability values are less than 5% level of significance (p-value < 0.05). This result is similar to thw studies of Hasan et al (2017) and Shahid et al (2017). On the other hand, 'Entrepreneurship course has enhanced my ability to identify opportunities (X2)', 'My university environment encourage me to engage in entrepreneurial activities (X4)', and 'The atmosphere at my university inspires me to develop new business ideas (X5)' are not statistically significant in influencing the level of entrepreneurial interest (Yi) of MBA students at 5% level of significance.…”
Section: 3supporting
confidence: 69%
“…Recent studies such as Durst and Sedenka (2016) in Sweden, Jabeen et al (2017) in United Arab Emirates, Shahid et al (2017) in Pakistan and Hasan et al (2017) in Bangladesh among others suggested that university environment where students learn plays a pivotal role in encouraging students to develop business ideas and start up their own business. This seems to help students mitigate any adverse impact that their negative perceptions that surrounds them might have on their entrepreneurial intentions (Shahid et el., 2017).…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these potential benefits of EE, it is not surprising that a multitude of programs have emerged that value and try to put into action these objectives. For example, Hasan et al (2017) have recognized that EE impacts both students and society. However, despite the importance of these programs and their widespread use, there is a lack of understanding of their effectiveness.…”
Section: Impact Of Entrepreneurial Educationmentioning
confidence: 99%
“…First, it compiles the programs on entrepreneurship education developed in Spain. Some previous studies have described entrepreneurial education programs (Maritz and Brown 2013;Maritz 2017), but usually did so in the university context (Hasan et al 2017) and, specifically, in the business field (Fayolle et al 2011;Musteen et al 2018), or in specific programs promoting entrepreneurship in other areas (Lans et al 2013; Barba-Sánchez and Atienza-Sahuquillo 2018). There have been a few studies that have developed a comprehensive review of programs in entrepreneurial education at non-university educational levels .…”
Section: Introductionmentioning
confidence: 99%